2012
DOI: 10.1111/j.1438-8677.2011.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic distinctiveness of metallicolous and non‐metallicolous populations of Armeria maritima s.l. (Plumbaginaceae) in Poland

Abstract: Patterns of morphological, genetic and epigenetic variation (DNA methylation pattern) were investigated in metallicolous (M) and non-metallicolous (NM) populations of Armeria maritima. A morphological study was carried out using plants from six natural populations grown in a greenhouse. Morphological variation was assessed using seven traits. On the basis of this study, three representative populations were selected for molecular analyses using metAFLP to study sequence- and methylation-based DNA variation. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 68 publications
(118 reference statements)
2
31
0
1
Order By: Relevance
“…Some of these soils are so rich in Zn that excess of this nutrient becomes a major factor limiting plant growth (Ernst 2006) and only some plants were able to adapt to such extreme environments (e.g. Przedpelska and Wierzbicka 2007;Abratowska et al 2012). It is highly probable that Zn metabolism and the impact of this metal on physiological processes could be different in plants from Zn-poor and Zn-rich soils.…”
Section: Stimulation Of the Onset Of Flowering By Low Zn Concentrationsmentioning
confidence: 99%
“…Some of these soils are so rich in Zn that excess of this nutrient becomes a major factor limiting plant growth (Ernst 2006) and only some plants were able to adapt to such extreme environments (e.g. Przedpelska and Wierzbicka 2007;Abratowska et al 2012). It is highly probable that Zn metabolism and the impact of this metal on physiological processes could be different in plants from Zn-poor and Zn-rich soils.…”
Section: Stimulation Of the Onset Of Flowering By Low Zn Concentrationsmentioning
confidence: 99%
“…MetAFLP platforms proved to be a valuable tool for analyzing changes induced by cryopreservation in Gentiana cruciata tissue (Mikuła et al 2011), or for evaluating the genetic distinctiveness of metallicolous and non-metallicolous populations of Armeria maritime (Abratowska et al 2012). Population genetic analysis of Poa annua (Chwedorzewska and Bednarek 2012) demonstrated that the approach could be used to extract information on epigenetic variation even in the case of population studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nickel could lead to modification missing in histone H2A, H2B, H3, and H4, and bring about increased demethylation of H3K9 and generally improved ubiquitination level of H2A and H2B [16,17,18,19,20,21,22,23,24]. The plant genomic DNA changed and rapidly responded to the environmental stress such as chilling, salts, heavy metal and pollutants [25,26,27]. The heritable methylation and phenotypic variations in these responses have been much vital for the research of plant breeding.…”
Section: Discussionmentioning
confidence: 99%